Corruption as a Cultural Phenomenon? Analyzing Corruption Issues in Economics, Politics, Education and the Public Sector - Muhammad Safuan Yusoff; Irma Wani Othman; Hidayah Iwani Mohd Kamal (Human Resource Management Academic Research Society (HRMARS), 2023)
Corruption has presently evolved into a topic of paramount concern across the spheres of economics, politics, education, and the public sector. The government is deeply committed to addressing this issue, recognizing it as one of the most intractable social phenomena or crimes in the nation, surpassing even other social predicaments such as drug abuse. The pivotal question revolves around the underlying reasons for the persistence of this phenomenon. Notably, this issue encompasses not only low-ranking officials but also individuals who have achieved remarkable status and prestige within society. Thus, the primary objective of this study is to dissect the root causes of corruption prevalent in contemporary society. This research identifies the contributing factors, repercussions, and government initiatives aimed at tackling this issue. Four fundamental issues are brought to the forefront within this paper: (i) corruption in economics, (ii) corruption in politics, (iii) corruption in education, and (iv) corruption in the public sector. The qualitative research method is employed in crafting this paper, grounded in the positivist philosophy, and serves to explore the practice of corruption as a cultural phenomenon. Data collection and amalgamation techniques are instrumental in furnishing inductive or qualitative data analysis. The outcomes of this research chiefly emphasize broader connotations. Utilizing the qualitative method, academic journals previously published, and information acquired from official government and non-government websites are harnessed as research materials to accumulate data and information pertinent to the issue of corruption. A comprehensive review of the literature conducted within this study explicates that corruption emanates from the unprofessional conduct of an individual.